Characterization of typical surface effects in additive manufacturing with confocal microscopy. (8th January 2015) - Grimm, Tobias; Wiora, Georg; Witt, Gerd
Abstract: The surfaces of laser-sintered and laser beam melted parts are characterized by typical surface effects and thus cause difficulties when using the popular tactile profilometry method and conventional two-dimensional surface parameters for analysis. Therefore, this study shows the potential of a new measurement approach by a confocal microscope and three-dimensional surface parameters. Within this study, a special focus is laid on the classification of different surface orientations and on a special issue in laser sintering: orange peel severity.